2021
DOI: 10.1016/j.chest.2021.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Circulating Tumor DNA in Identifying Somatic Mutations and Tracking Tumor Evolution in Patients With Non-small Cell Lung Cancer

Abstract: BACKGROUND:The usefulness of circulating tumor DNA (ctDNA) in detecting mutations and monitoring treatment response has not been well studied beyond a few actionable biomarkers in non-small cell lung cancer (NSCLC).RESEARCH QUESTION: How does the usefulness of ctDNA analysis compare with that of solid tumor biopsy analysis in patients with NSCLC? METHODS: We retrospectively evaluated 370 adult patients with NSCLC treated at the City of Hope between November 2015 and August 2019 to assess the usefulness of ctDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Therefore, it is of great importance to seek an alternative method as a supplement to radiological imagination in precision oncology. Numerous studies have found that quantification of baseline ctDNA predicted prognosis of patients harboring EGFR mutations 17,18 . Recent studies have shown that ctDNA clearance was of prognostic significance, in which molecular responders with undetectable ctDNA after targeted therapy had significantly longer survival than non‐responders 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of great importance to seek an alternative method as a supplement to radiological imagination in precision oncology. Numerous studies have found that quantification of baseline ctDNA predicted prognosis of patients harboring EGFR mutations 17,18 . Recent studies have shown that ctDNA clearance was of prognostic significance, in which molecular responders with undetectable ctDNA after targeted therapy had significantly longer survival than non‐responders 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that quantification of baseline ctDNA predicted prognosis of patients harboring EGFR mutations. 17,18 Recent studies have shown that ctDNA clearance was of prognostic significance, in which molecular responders with undetectable ctDNA after targeted therapy had significantly longer survival than non-responders. 19,20 Therefore, molecular evaluation of ctDNA clearance helps to identify a group of patients that would benefit from EGFR-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutations, notably the KRAS G12C mutation, can be identified from tissue samples (bronchial biopsies, transthoracic biopsies, and more rarely biopsies from a metastatic site or a surgically resected sample), from different cytological and fluid samples (bronchial aspirates, fine needle aspiration, endobronchial ultrasound and transbronchial needle aspiration, bronchoalveolar lavage, pleural and cerebrospinal fluid) and from blood [ 15 , 105 , 185 , 186 , 187 , 188 , 189 ]. These mutations are currently being characterized using targeted sequencing (RT-PCR and droplet digital PCR) or next-generation sequencing (NGS) approaches [ 189 , 190 ]. Moreover, liquid biopsy is certainly a very promising tool to use at baseline but also at progression in patients treated with specific inhibitors of KRAS G12C mutations to track new KRAS mutations, notably the Y96D mutation, as well as other mutations such as the R86S and H95D mutations [ 141 ].…”
Section: Biological Samples and Molecular Testingmentioning
confidence: 99%
“…In case of an inconclusive result, and if possible, depending on the patient status and tumor site, a tissue re-biopsy should be done to track resistance mechanisms [ 206 ]. NGS approaches can routinely use a LB and thus provide access to the KRAS status and associated genomic alterations [ 15 , 190 , 214 , 215 , 216 , 217 ]. However, NGS with a LB is currently not often available in most laboratories, in Europe at least, and is set up for routine testing in only a few comprehensive cancer centers [ 191 , 215 , 218 ].…”
Section: Opportunities and Challenges For The Thoracic Pathologistsmentioning
confidence: 99%
“…[115][116][117][118] Accordingly, baseline and posttreatment ctDNA indicated worse clinical outcomes. [119][120][121][122] Circulating tumor DNA has also been investigated in the evaluation of tumor mutation burden (TMB), a novel predictive marker reflecting the total number of existing mutations, which is thought to be predictive of the response to PD-1 and PD-L1 inhibitors. It was hypothesized that patients with a higher burden of somatic mutations would benefit from immune checkpoint inhibitors due to a better recognition of neoantigens.…”
Section: Circulating Tumor Dnamentioning
confidence: 99%